The Effects of Positive End-Expiratory Pressure on Transpulmonary Pressure and Recruitment–Derecruitment During Neurally Adjusted Ventilator Assist: A Continuous Computed Tomography Study in an Animal Model of Acute Respiratory Distress Syndrome - Widing, Carl Hannes; Pellegrini, Mariangela; Larsson, Anders; Perchiazzi, Gaetano (Frontiers in Physiology, 2019)
Background Whether spontaneous breathing (SB) should be used in early acute respiratory distress syndrome (ARDS) is questioned because it may cause ventilator-induced lung injury (VILI) by tidal high strain/stress and recruitment/derecruitment (R/D). However, SB has shown beneficial effects when used appropriately. We hypothesized that high levels of positive end-expiratory pressure (PEEP), during assisted SB, would prevent tidal R/D, reducing ventilatory variation and respiratory rate while potentially increasing transpulmonary pressure (PTP). The aim was to test this hypothesis in experimental mild ARDS during continuous SB using neurally adjusted ventilator assist (NAVA) and uninterrupted computed tomography (CT) exposure. Methods Mild experimental ARDS (PaO2/FiO2-ratio of 250) was induced in anesthetized pigs (n = 5), ventilated using uninterrupted NAVA. PEEP was changed in steps of 3 cmH2O, from 0 to 15 and back to 0 cmH2O. Dynamic CT scans, ventilatory parameters, and esophageal pressure were acquired simultaneously. PTP and R/D were calculated and compared among PEEP levels. Results When increasing PEEP from 0 to 15 cmH2O, tidal R/D decreased from 4.3 ± 5.9 to 1.1 ± 0.7% (p < 0.01), breath-to-breath variability decreased, and PTP increased from 11.4 ± 3.7 to 29.7 ± 14.1 cmH2O (R2 = 0.96). Conclusion This study shows that injurious phenomena like R/D and high PTP are present in NAVA at the two extremes of the PEEP spectrum. Willing to titrate PEEP to limit these phenomena, the physician must choose the best compromise between restraining the R/D or PTP.